Microstructure Evolution and Cation Interdiffusion in Thin Sm2O3 Films on CeO2 Substrates. Issue 10 (24th July 2014) - Rockenhäuser, Christian; Butz, Benjamin; Störmer, Heike; Gerthsen, Dagmar; Chan, H.
<x xml:space="preserve">Abstract</x> Samaria (Sm2O3) thin films with a thickness of 180 nm were deposited on polycrystalline CeO2 substrates by pulsed layer deposition to study phase formation and bulk cation interdiffusion in the Ce1−xSmxO2−x/2 system after annealing at temperatures between 987°C and 1266°C. Transmission electron microscopy combined with electron diffraction and analytical techniques was applied for phase determination. The cubic fluorite and cubic bixbyite phases were observed at low and intermediate Sm concentrations. The monoclinic phase occurs only at very high Sm concentrations due to the low Ce‐solubility in Sm2O3. Furthermore, a cubic phase with I213 structure was observed at higher Sm concentrations. Cation interdiffusion coefficients were derived from Sm concentration profiles across the Sm2O3/CeO2 interface using the diffusion–couple solution of the diffusion equation. The temperature dependence of interdiffusion coefficients is well described by an Arrhenius‐type relation, which yields an activation enthalpy of 2.26 eV/atom for bulk cation interdiffusion.